Combating non-communicable diseases in rural Lucknow: Are the skills and knowledge of female health workers adequate? - Saini, Arunima; Agarwal, Monika (International Journal Of Community Medicine And Public Health, 2020)
Background: India is facing the surging trend of non-communicable diseases (NCD). Forecasting the burden for NCDs, the Government of India (GOI) initiated a program in 2010 across the country, i.e., National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases, and Stroke. The GOI has envisaged the female health workers (FHW) for the last mile delivery of health services under the programme. Available literature shows that FHWs lack essential knowledge regarding chronic diseases. This study attempts to fill these gaps by studying knowledge and skills regarding NCDs among FHWs in rural Lucknow. Objectives were to explore the knowledge about NCDs among ASHAs and ANMs in rural Lucknow and to assess of skills related to NCD screening among ANMs in rural Lucknow. Methods: It was a cross-sectional study conducted among FHWs of Lucknow, Uttar Pradesh from June 2019 to August 2019. Results: Among the FHWs, knowledge about NCDs was found to be higher for those with the age more than 40 years, with the education of higher secondary and above and also amongst those who had received previous training for NCDs. Conclusions: Majority of the respondents were found to have poor knowledge regarding NCDs. Additionally, older age, training and higher education are found to be associated with good knowledge; there is a need of training of grass root level workers for them to correctly identify the symptoms and risk factors of various NCDs.